Students at the Center: Insights and Implications of Authentic, 5E Instruction in High School English Language Arts - Jeter, Gage; Baber, Jane; Heddy, Benjamin; Wilson, Scott; Williams, Leslie; Atkinson, Linda; Dean, Sharon; Gam, Gregg (Frontiers in Education, 2019)
This paper explores the 5E model of lesson design (engage, explore, explain, extend, evaluate) in English Language Arts (ELA) classrooms in consideration of an authentic teaching and learning framework. This quasi-experimental pre and post intervention study centers on student motivation and academic emotions regarding direct instruction in comparison to an authentic, 5E lesson. When comparing pre and post conditions across two types of instructional methods (direct instruction and authentic, 5E lessons), findings suggest students are less interested and more bored when participating in direct instruction experiences. Moreover, academic pressure increased in the authentic group while classroom mastery decreased.